Perlindungan Hukum Bagi Kreditur Dengan Hak Tanggungan Terhadap Objek Jaminan Yang Terlantar - Silva Fransisca Utami; Rosalinda Elsina Latumahina (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
The designation of collateral—specifically land—as "abandoned land" creates legal issues, as it can compromise legal certainty and the protection of the creditor's rights as the security holder. This study aims to analyze the legal protection afforded to creditors in such situations and to examine the legal measures available to safeguard their interests. The study employs a normative legal research method, utilizing statutory, conceptual, and legislative approaches. The findings indicate that while security rights grant creditors priority, the designation of collateral as abandoned land can diminish or even eliminate its value if the land rights are revoked or seized by the government in accordance with applicable laws. Consequently, legal protection for creditors must be ensured through legal certainty, the careful application of credit principles, coordination between land offices and financing institutions, and the availability of mechanisms—such as approval processes or legal recourse—to address abandoned land designations that could prejudice creditors' rights. Therefore, clearer and more balanced regulations are required to ensure that the state's interest in designating land as abandoned remains aligned with the protection of creditors' rights as security holders.